Loop-Mediated Isothermal Amplification Assay for Detection of Generic and Verocytotoxin-Producing Escherichia coli among Indigenous Individuals in Malaysia - Ju, C.S.J.; Chua, K.H.; Lim, Yvonne Ai Lian; Lee, S.C.; Thong, Kwai Lin (Hindawi Publishing Corporation, 2014)
We have successfully developed a Loop-mediated isothermal amplification (LAMP) assay that could specifically detect generic Escherichia coli (E. coli). This assay was tested on 85 bacterial strains and successfully identified 54 E. coli strains (average threshold time, Tt = 21.26). The sensitivity of this assay was evaluated on serial dilutions of bacterial cultures and spiked faeces. The assay could detect 102 CFU/mL for bacterial culture with Tt = 33.30 while the detection limit for spiked faeces was 103 CFU/mL (Tt = 31.12). We have also detected 46 generic E. coli from 50 faecal samples obtained from indigenous individuals with 16% of the positive samples being verocytotoxin-producing E. coli (VTEC) positive. VT1/VT2 allele was present in one faecal sample while the ratio of VT1 to VT2 was 6 : 1. Overall, our study had demonstrated high risk of VTEC infection among the indigenous community and most of the asymptomatic infection occurred among those aged below 15 years. The role of asymptomatic human carriers as a source of dissemination should not be underestimated. Large scale screening of the VTEC infection among indigenous populations and the potential contamination sources will be possible and easy with the aid of this newly developed rapid and simple LAMP assay.